Treosulfan-Based Conditioning Regimen for Hematopoietic Stem Cell Transplantation in Pediatric Patients with Hemophagocytic Lymphohistiocytosis - Ho Joon Im; Sung Han Kang (The Korean Society of Pediatric Hematology-Oncology, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a fatal disease unless timely and effective treatment is given. Immunochemotherapy including etoposide, with or without hematopoietic stem cell transplantation (HCT), has improved the outcomes for patients with HLH. In patients with familial or refractory HLH, HCT is now routinely performed and is the only curative treatment. Conditioning regimens play an important role in the success of HCT for pediatric patients with HLH and other non- malignant diseases and have improved dramatically in recent decades. The initial HCT approach using myeloablative conditioning significantly improved the outcomes of patients with HLH but was associated with considerable transplant-related mortality. A subsequent strategy using reduced-intensity conditioning (RIC) remarkably reduced the incidence of TRM. However, the high level of mixed chimerism associated with RIC has prompted the search for improved conditioning regimens. Recently, treosulfan has replaced busulfan as a component of a reduced toxicity conditioning regimen. Both its myeloablative and immunosuppressive properties, as well as a favorable toxicity profile, make treosulfan a potential candidate for use as part of conditioning regimen prior to HCT. Indeed, treosulfan-based conditioning regimens are being increasingly used in pediatric patients with various non-malignant diseases. We here review the recent progress in HCT for pediatric HLH with a focus on treosulfan-based conditioning regimens, including our own experience.